Microfinance services and the growth of women entrepreneurial businesses in North Central Nigeria - Amechi Fabian Anoke (Goodwood Publishing, 2023)
Purpose: This study examined the effect of microfinance services on the growth of Women's entrepreneurial businesses in North-central Nigeria. Research methodology: A survey research design with a population of 7061 women entrepreneurs in North-central, Nigeria and a sample size of 379 was used in the study. The effect between the variables was determined through correlation and multiple regression analysis. Results: The findings revealed that microfinance lending; saving and training services have positive and weighty effects on the growth of women entrepreneurial businesses in Nigeria’s North-central while microfinance management consultancy services recorded an inverse and insignificant impact on the women entrepreneurial businesses' growth in the zone. Limitations: This study is limited to only entrepreneurial women in Nigeria’s North-central with lending services, training services, saving services, and consultancy services as proxies for MFIs services; there are other services provided by MFIs like insurance that are not covered by this study. Contribution: This study incorporated management consultancy services as one of the variables which have hitherto been neglected or ignored in the models that are to explain the microfinance services in Nigeria.